Urgency of Standardizing Audio Representation in Visually Impaired Students’ Fraction Learning - Muhtarom Nur Rasyid; Tatang Herman; Aan Hasanah (Jurnal Karya Pendidikan Matematika, 2026)
This research investigated the necessity of standardizing the audio representation method of mathematical notations in fraction learning among students with visual impairments. A descriptive qualitative case study design was used to collect data by observing classroom situations and conducting semi-structured interviews with one mathematics teacher and three visually impaired students at a state special school in West Java, Indonesia. Thematic analysis extracted four general themes: systemic variance in symbol notation practice, structural ambiguity leading to interpretation errors, institutional lack of symbol standardization frameworks, and multivariate rationales for standardization. The findings showed that variations in audio representation significantly affected students’ understanding, particularly for mixed fractions and multi-level expressions. Estimation errors worsened with increased complexity, ranging from 97% accuracy for simple fractions to just 15% for multi-operation expressions. Consequently, this research suggests the development of Indonesian MathSpeak guidelines and the implementation of multi-school trials to adopt uniform audio representation standards, ensuring equitable mathematics learning experiences for visually impaired students.